Preliminary data for performance in hue ordering tests during pregnancy - T.S.S. Calandrini (Brazilian Journal of Medical and Biological Research, 2019)
The visual system of women changes during pregnancy. Few reports have addressed the effects of pregnancy on color vision. We aimed to compare the color vision of women in the first, second, and third trimesters of pregnancy. Fifty women were divided into first (n=10), second (n=10), third trimester pregnancy groups (n=10), and non-pregnant group (n=20). We used the Farnsworth D15 and Lanthony desaturated D15 (D15d) tests. The hue ordering quantified the amount of error (C-index) and the chromatic selectivity of the errors (S-index). Bland-Altman analysis was applied to the hue ordering data. No difference was found for Farnsworth D15 test results obtained from the pregnant groups and the non-pregnant group (P<0.0083). For the Lanthony D15 desaturated test, the third trimester pregnant group had higher C-index and S-index than non-pregnant women and first-trimester pregnant women (P<0.0083). The Bland-Altman analysis showed that the limits of agreement increased as pregnancy advanced, and the errors were biased to the D15d test. In this study, color vision was impaired during pregnancy. Color vision evaluation could be used as an indicator of the functional status of the central vision during pregnancy.